Apokaliptično dojemanje stvarnosti v drami Mihaila Bulgakova Beg - Kaloh Vid, Natalia (Slavia Centralis, 2020)
Apocalyptic comprehension of reality in Mikhail Bulgakov’s drama FlightThe article analyzes the historical and philosophical position of Mikhail Bulgakov as reflected in the drama Beg, which depicts the last days of the civil war in Russia. The author states that Bulgakov's creative vision is influenced by apocalyptic thinking. The drama is based on Revelation and includes numerous allusions to the apocalyptic prophecy. As a result of the historical apocalypse, the norms of the previous life are destructed. The destruction of the old world is signified by loss of homeland and identity as well as by the destruction of the human soul.
Keywords: Bulgakov; drama Beg; Beg; revelation; allusion